Estudo do nível de infecção por Babesia bovis e Babesia bigemina em bovinos da raça Canchim naturalmente infestados com o carrapato Rhipicephalus (Boophilus) microplus - Bilhassi, Talita Barban [UNESP] (2016)
Among the main causes of production losses in cattle is in the tropics infestation by Rhipicephalus (Boophilus) microplus, and consequently the hemoparasites transmitted by it. The resistance of zebu and crossbred with European breeds to infestation by this mite is widely known. However, as regards susceptibility to bovine babesiosis, there is evidence that genetic group can also interfere in resistance following the same pattern observed in the tick vector, with the taurine presenting greater sensitivity. This study aimed to evaluate parasitaemia by Babesia bovis and Babesia bigemina in 50 heifers Canchim (⅝ Charolais + ⅜ Zebu) naturally infested by R. (B.) microplus in four seasons for 24 months, and characterize the profile of cytokines that may be associated with phenotype resistance and susceptibility by gender hemoparasites Babesia spp. Adult female ticks counts with size equal to or greater than 4.5 mm in diameter, present in the left side of each calf were performed. The extracted DNA samples were subjected to amplification by Reaction Polymerase Chain Quantitative Real Time (qPCR), using primers flanking fragments of mitochondrial gene cytochrome B (mt-cyt B) specific for B. bovis and B. bigemina. The RNA extracted from the blood was used to synthesize complementary DNA (cDNA) for expression analysis of genes IFN-γ, TNF-α, IL-10 and IL-12B by relative quantification (RT-qPCR). Significant differences were observed (P <0.05) between the months of reviews for the tick count. However, there was no significant effect (P>0.05) in samples taken between november 2013 and january 2014 and between the months january and february 2015. The frequency of parasitaemia in the herd was 98%. Among the samples of DNA that could be quantified by qPCR, 98% and 95.4% were positive for B. bovis and B. bigemina, respectively. Regarding the number of copies (NC) of fragments of genes mt-cyt B, specific to B. bovis and B. bigemina significant effects were observed (P<0.05) for both species and interaction between those harvests in different seasons. Analysis of the mRNA expression level of IFN-γ, TNF-α and IL-12B showed that there was a significant effect (P<0.05) interaction between the animal extreme resistance/susceptibility and seasons, except for IL-10. It is concluded that the qPCR has high sensitivity and specificity for the diagnosis of bovine babesiosis in blood samples and that the fluctuation in the parasitic load in the different seasons of the year may be associated with the profile of cytokine expression presented by herd animals Canchim during the experimental period.